2021
DOI: 10.1007/s00402-020-03743-6
|View full text |Cite
|
Sign up to set email alerts
|

Injury epidemiology in men’s professional team sports: is media analysis helpful?

Abstract: Introduction Epidemiological injury surveillance in professional sports is often based on online media analysis in order to collect necessary data. However, the validation of this study protocol is lacking. Therefore, this study aimed to identify the validity of injury surveillance in men’s professional team sports based on media reports. Methods In a retrospective cohort study, the validity of media-data-relating injuries was investigated in participating… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…This study included complete data samples of ACL injuries based on high‐validity insurance data, which could be a reason for injury rate differences. Other study designs such as patient registries or media analyses often underestimate the actual injury prevalence [3, 20, 33, 57].…”
Section: Discussionmentioning
confidence: 99%
“…This study included complete data samples of ACL injuries based on high‐validity insurance data, which could be a reason for injury rate differences. Other study designs such as patient registries or media analyses often underestimate the actual injury prevalence [3, 20, 33, 57].…”
Section: Discussionmentioning
confidence: 99%
“…There are existing studies showing that media-based injury data are valid, especially for severe injury types such as ACL injuries, with a validity of 100% [ 14 ]. Nevertheless, for all media-reported knee injuries together, the validity was only 78.2%, with a clear trend for reduced evidence of media analysis for less severe injuries [ 14 , 25 ]. However, by pooling the media-reported data together with the player-reported data, the validity of a parameter such as “days missed due to knee-related injury” is as good as it can be.…”
Section: Discussionmentioning
confidence: 99%
“…com). When a player who is under contract in one of the larger European leagues misses one or more matches due to an injury, this injury is reported by "Transfermarkt" based on different sources [14,25]. These media-reported knee injuries were matched with those recorded by player anamnesis and medical history.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The International Olympic Committee (IOC) has recently defined sports injuries as new or recurring musculoskeletal complaints occurred during competition or training and requiring medical attention [10]. However, acute sport-related musculoskeletal injuries are characterized by a large heterogeneity in epidemiology and clinical presentation based on the sport performed [11,12]. Additionally, it has been reported that acute traumatic musculoskeletal injuries represent the 10-19% of all acute injuries treated in the emergency department [13,14].…”
Section: Introductionmentioning
confidence: 99%